All-fiber spatial rotation manipulation for radially asymmetric modes - Qi Mo (Nature Portfolio, 2017)
Abstract We propose and experimentally demonstrate spatial rotation manipulation for radially asymmetric modes based on two kinds of polarization maintaining few-mode fibers (PM-FMFs). Theoretical finding shows that due to successful suppression of both polarization and spatial mode coupling, the spatial rotation of radially asymmetric modes has an excellent linear relationship with the twist angle of PM-FMF. Both elliptical core and panda type FMFs are fabricated, in order to realize manageable spatial rotation of LP11 mode within ±360° range. Finally, we characterize individual PM-FMF based spatial orientation rotator and present comprehensive performance comparison between two PM-FMFs in terms of insertion loss, temperature sensitivity, linear polarization maintenance, and mode scalability.